Are outcome data regarding the survivors of neonatal care available from routine sources?. Issue 3 (1st November 1997) - Dawson, Catherine; Perkins, Martin; Draper, Elizabeth; Johnson, Ann; Field, David
Abstract : AIM: To determine whether existing information and surveillance systems can be used to provide follow up data on groups of infants at increased risk of disability—for example, the survivors of neonatal intensive care. METHODS: A survey was made of maternity, neonatal, and community child health information systems and surveillance programmes in the Trent Regional Health Authority. Children known to have received neonatal intensive care in Trent between 1 August 1992 and 31 July 1993, and a random sample of normal children in two health districts (data quality check) were included. A data linkage study was made to determine whether follow up information about a random sample of infants, known to be at increased risk of poor outcome, could be identified on community child health databases. Two widely accepted datasets (birth and 2 years) were used as standards for this exercise. The quality of data was audited. RESULTS: All clinical items of the birth minimum dataset were routinely recorded by at least one agency in each health district in Trent. Of the descriptive items, only the mother's age on leaving full time education was not collected. At 2 years, all clinical items were collected as part of the routine surveillance programme, but data were recorded using a system which severely limited interpretation. Data quality, in terms of the number of errors introduced at data entry, was very good with only 1.1% of the check items (4/368) incorrectly recorded. Only two districts had organised electronic transfer of data between maternity, neonatal, and community child health systems. The mother's NHS number, although available, was not routinely recorded by any system. The NHS number of the infant was routinely collected by six out of 12 community paediatric services. Data linkage was attempted in six districts with appropriate community child health databases. Just over 70% of the intensive care sample was successfully linked with follow up information on child health systems. CONCLUSIONS: The existing programmes for routine child surveillance could provide outcome data for high risk groups of infants, such as the survivors of neonatal intensive care. However, the present coding system used for data entry is inadequate. Furthermore, rates of identification, without the use of a unique identifier (NHS number) for each subject, are currently insufficient for monitoring health status in later life.